132PLiposomal irinotecan (nal-IRI) plus 5-fluorouracil/levoleucovorin (5 FU/LV) vs 5-FU/LV in Japanese patients (pts) with gemcitabine-refractory metastatic pancreatic cancer (mPAC). (24th November 2019) - Ioka, T; Nakamori, S; Sugimori, K; Kanai, M; Ikeda, M; Ozaka, M; Furukawa, M; Okusaka, T; Kawabe, K; Furuse, J; Komatsu, Y; Sato, A; et al.
Abstract: Background: In the NAPOLI-1 phase 3 trial, nal-IRI+5-FU/LV significantly increased median PFS (mPFS) vs 5-FU/LV (3.1 vs 1.5 months [mo], unstratified HR = 0.56, P = 0.0001) in pts with mPAC that progressed on prior gemcitabine-based therapy. This randomised phase 2 trial evaluated nalIRI+5FU/LV vs 5-FU/LV in Japanese pts with gemcitabine-refractory mPAC (NCT02697058). Methods: This study assessed nal-IRI+5-FU/LV tolerability as per the NAPOLI-1 dosing regimen (Part 1), and safety and efficacy (Part 2). Part 2 outcomes are reported. Pts were randomised 1:1 and stratified by KPS (70 and 80 vs ≥ 90) and baseline albumin (≥4.0 g/dL vs < 4.0 g/dL). Primary endpoint was PFS; secondary endpoints were ORR, DCR, OS, TTF, CA199 response and QoL. The ITT population comprised all pts randomised. Results: Differences in pt baseline characteristics were noted in the nal-IRI+5-FU/LV (n = 40/79) vs 5FU/LV (n = 39/79) arms, e.g. hepatic lesions (63% vs 51%), stage IV disease at diagnosis (78% vs 51%), and post-study anticancer therapy (55% vs 72%). Efficacy results are shown in the table. Investigator-assessed mPFS increase with nal-IRI+5-FU/LV was clinically meaningful and statistically significant vs 5-FU/LV (2.7 vs 1.5 mo, P = 0.039). Independently-assessed mPFS showed a similar trend (1.7 vs 1.6 mo, P = 0.376). mOS was 6.3 mo with nal-IRI+5-FU/LV and not reached with 5-FU/LV. DCR, TTF, CA19-9 and ORR response increased, ORR significantly, with nalIRI+5-FU/LV vs 5-FU/LV. The most commonly reported grade ≥3 TEAEs with nal-IRI+5-FU/LV vs 5-FU/LV were decreased neutrophil count (37% vs 3%), decreased white blood cell count (20% vs 0) and diarrhoea (17% vs 3%). Conclusions: Treatment with nal-IRI+5-FU/LV was associated with clinically meaningful and statistically significant gains in investigator-assessed mPFS and ORR vs 5-FU/LV in Japanese patients, with no new or unexpected safety signals in this population. Clinical trial identification: NCT02697058. Editorial acknowledgement: Medical writing support was provided by Christopher Lamb of Physicians World Europe GmbH, Mannheim, Germany and was funded by Servier Global Medical Affairs (Suresnes, France). Legal entity responsible for the study: Servier and the authors. Funding: Servier. Disclosure: T. Ioka: Advisory / Consultancy: Shire. M. Kanai: Advisory / Consultancy, Shareholder / Stockholder / Stock options: TheraBioPharma Inc. M. Ikeda: Advisory / Consultancy: Shire; Advisory / Consultancy, Research grant / Funding (self): Bayer Yakuhin; Advisory / Consultancy, Research grant / Funding (self): Eisai; Advisory / Consultancy: Novartis Pharma; Advisory / Consultancy: MSD; Research grant / Funding (self): Kyowa Hakko Kirin; Research grant / Funding (self): Yakult; Research grant / Funding (self): Eli Lilly Japan; Research grant / Funding (self): Ono pharmaceutical; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Baxalta Japan Limited; Research grant / Funding (self): Chugai Pharmaceutical; Research grant / Funding (self): Bristol-Myers Squibb; Research grant / Funding (self): Merck Serono; Research grant / Funding (self): Nano Carrier; Research grant / Funding (self): ASLAN Pharmaceuticals; Research grant / Funding (self): Novartis Pharma; Research grant / Funding (self): Takar Bio. T. Okusaka: Honoraria (self): Meiji Seika Pharma ; Honoraria (self): MSD; Honoraria (self): AbbVie Inc.; Honoraria (self), Research grant / Funding (self): Eisai Co., Ltd.; Honoraria (self): Yakult Honsha Co., Ltd.; Honoraria (self): Shire; Honoraria (self): ; Honoraria (self): Daiichi Sankyo Co., Ltd.; Honoraria (self): Taiho Pharmaceutical Co., Ltd; Honoraria (self): Takeda Pharmaceutical Co., Ltd.; Honoraria (self): Chugai Pharmaceutical Co., Ltd.; Honoraria (self): Teijin Pharma Ltd.; Honoraria (self): Eli Lilly Japan K.K.; Honoraria (self): Novartis Pharma K.K.; Honoraria (self): Nobelpharma Co., Ltd.; Honoraria (self): Bayer Yakuhin, Ltd.; Honoraria (self): Pfizer Japan Inc.; Honoraria (self): FUJIFILM RI Pharma Co., Ltd ; Honoraria (self), Research grant / Funding (self): Bristol-Myers K.K.; Research grant / Funding (self): AstraZeneca K.K.; Research grant / Funding (self): Baxter. J. Furuse: Advisory / Consultancy: Shire. Y. Komatsu: Advisory / Consultancy: Yakult; Advisory / Consultancy: Taiho; Advisory / Consultancy: Lilly. S. Shimizu: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Incyte Corporation; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): Baxalta Japan; Research grant / Funding (institution): Taiho Pharmaceutical; Research grant / Funding (institution): Sumitomo Dainippon Pharma; Research grant / Funding (institution): Yakult; Research grant / Funding (institution): IQVIA Services Japan. P. Chugh: Full / Part-time employment: Servier. R. Tang: Full / Part-time employment: Servier. M. Ueno: Honoraria (self), Research grant / Funding (institution): Taiho Pharmaceutical; Honoraria (self): Yakult Honsha; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self): Novartis; Honoraria (self): Lilly; Honoraria (self): Teijin Pharma; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Shire; Honoraria (self), Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Merck Serono; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): MSD; Research grant / Funding (institution): NanoCarrier; Research grant / Funding (institution): Dainippon Sumitomo Pharma; Research grant / Funding (institution): Incyte; Research grant / Funding (institution): ASLAN Pharmaceuticals. All other authors have declared no conflicts of interest.